Bacterial Nanocellulose based Wound Dressings: Current and Future Prospects - Chopra, Hitesh; Gandhi, Shweta; Gautam, Rupesh K.; Kamal, Mohammad Amjad (Current Pharmaceutical Design, 2022)
Although there are many treatment options available for wound and burns dressings, improvements in technology are still required. Bacterial cellulose is a polymer derived from the microbiological world and has shown some promising properties that recommend it as a wound healing therapeutic. Moreover, bacterial cellulose can be nanosized to form Bacterial Nanocellulose (BNC), enhancing its properties. Most importantly, in addition to its inherent antibacterial properties, BNC can be used to deliver drugs. This article presents a birds-eye view of the preparation method and applications of BNC-based wound dressings.
Keywords: Bacterial nanocellulose